2010
DOI: 10.1111/j.1540-8159.2010.02858.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryoablation versus Radiofrequency Ablation for Atrioventricular Nodal Reentrant Tachycardia: Patient Pain Perception and Operator Stress

Abstract: CRYO, as compared with RF, produces less pain in patients and less stress in operator in the treatment of AVNRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 19 publications
0
36
0
Order By: Relevance
“…In both studies, pain perception was significantly less among patients treated with cryoablation than among those treated with RF ablation (VAS 0–10: 2.3 ± 2.8 vs 5.4 ± 3.4, P = 0.024; Ref. , and VAS 0–100: 7.3 ± 13.9 vs 20.3 ± 22.0, P < 0.001; Ref. ).…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…In both studies, pain perception was significantly less among patients treated with cryoablation than among those treated with RF ablation (VAS 0–10: 2.3 ± 2.8 vs 5.4 ± 3.4, P = 0.024; Ref. , and VAS 0–100: 7.3 ± 13.9 vs 20.3 ± 22.0, P < 0.001; Ref. ).…”
Section: Resultsmentioning
confidence: 86%
“…Two RCTs measured patient pain perception using different visual analog scales (VAS), one ranging from 0 to 10 and the other ranging from 0 to 100 . In both studies, pain perception was significantly less among patients treated with cryoablation than among those treated with RF ablation (VAS 0–10: 2.3 ± 2.8 vs 5.4 ± 3.4, P = 0.024; Ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other benefits include cryoadhesion and catheter stability, clearly demarcated lesion edge, and lower incidence of thromboembolism and coronary artery damage . A recent study also showed that cryoablation produces less pain in patients and is less stressful for the operators in the treatment of AVNRT . Acute procedural success rates of cryoablation have been reported to be between 85–96.8% .…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of PACE , 1 Chan and colleagues compare radiofrequency (RF) and cryo ablation for atrioventricular nodal reentry tachycardia (AVNRT) ablation. The authors draw attention to the stresses on both the patient and on the operator.…”
mentioning
confidence: 99%